Evaluating the Teaching Performance in the English Language Proficiency Program at Al-Ahgaff University in the Light of Quality Assurance Standards from Students' Perspectives - Al-Bouri, Mohammed Salim Karamah; Almuslimi, Fazee Khalid Alezi Mohammed; Alfalagg, Abdullah Rajab (International Journal of Language and Literary Studies, 2025)
English Language Proficiency Programs (ELPPs) have proliferated in Yemeni tertiary institutions due to the Ministry of Higher Education's requirement that all students intending to enroll in graduate programs in Yemen should obtain certification in the English language. The present study aims to evaluate the teaching performance in the ELPP at Al-Ahgaff University in light of quality assurance standards. It investigates students' perceptions of implementing the indicators of teaching performance based on quality assurance standards in the ELPP. This study employed a descriptive quantitative method, utilizing a questionnaire distributed to the participants to assess the implementation of quality assurance standards in teaching performance. To achieve the objectives of the study, 162 students responded to a closed-ended questionnaire in which the collected data were quantitatively analysed through the SPSS program. Descriptive and inferential statistical measures were computed to analyze the respondents' responses. The findings showed that (10) of the teaching performance indicators were as highly implemented while the other six indicators were moderately implemented by the teachers in the ELPP. The results also revealed significant differences in the students' perceptions of implementing the indicators attributed to gender, in favor of female students. However, no statistically significant differences appeared due to the participants' level of study. Such significant implications were categorized based on resource demand and potential impact for developing English language proficiency programs.